ปัจจัยที่มีผลต่อความต้องการใช้ข้อมูลทางการบัญชีในการตัดสินใจด้านกิจกรรม ทางการตลาดของวิสาหกิจขนาดกลางและขนาดย่อมในจังหวัดสมุทรปราการ - อธิรัฐจิรชัย, ณัฐธยาน์ (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2016)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาปัจจัยที่มีผลต่อความต้องการใช้ข้อมูลทางการบัญชีที่เป็นประโยชน์ต่อการตัดสินใจในด้านกิจกรรมทางการตลาดของวิสาหกิจขนาดกลางและขนาดย่อมในจังหวัดสมุทรปราการ ประชากรที่ใช้ในการศึกษาได้แก่ หัวหน้าฝ่ายการตลาดและเจ้าของกิจการของวิสาหกิจขนาดกลางและขนาดย่อมในจังหวัดสมุทรปราการ จำนวน 208 ชุด โดยสุ่มตัวอย่างมา 130 คนเครื่องมือที่ใช้ในการเก็บรวมรวม คือ แบบสอบถาม สถิติที่ใช้ในการวิจัย ได้แก่ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน สัมประสิทธิ์สหสัมพันธ์อย่างง่าย และการวิเคราะห์ถดถอยพหุคูณผลการวิจัย พบว่า 1) หัวหน้าฝ่ายการตลาดมีอายุประมาณ 20-25 ปี มีวุฒิการศึกษาระดับปริญญาตรี ประสบการณ์ในสายงานการตลาดส่วนใหญ่น้อยกว่า 3 ปี สถานประกอบการ มีระยะเวลาการเปิดดำเนินงานส่วนใหญ่ 6-10 ปี ลักษณะของสถานประกอบส่วนใหญ่เป็นกิจการบริการ คุณสมบัติของข้อมูลทางการบัญชีที่ผู้ประกอบการต้องการได้แก่ความเชื่อถือได้ 2) ความต้องการใช้ข้อมูลทางการบัญชีโดยภาพรวมและรายด้านอยู่ในระดับมาก 3) ความต้องการใช้ข้อมูลทางการบัญชี ทั้งโดยรวมและรายด้าน มีความสัมพันธ์กันในทางบวก 4)ตัวแปรปัจจัยที่มีผลต่อความต้องการใช้ข้อมูลทางการบัญชีได้อย่างมีนัยสำคัญทางสถิติมี 2 องค์ประกอบได้แก่ การวิเคราะห์จุดคุ้มทุน(X18) และราคาของผู้แข่งขัน(X21)ซึ่งสามารถเขียนเป็นสมการได้ดังนี้ สมการในรูปแบบคะแนนดิบ Y^ = 1.141+0.31(X18) + 0.23(X21) สมการในรูปแบบคะแนนมาตรฐาน Z^ = 0.065(Z18) + 0.053(Z2) FACTORS AFFECTING THE DEMAND FOR USING ACCOUNTING INFORMATION FOR DECISION MAKING ON MARKETING ACTIVITY OF SMALL AND MEDIUM ENTERPRISES IN SAMUTPRAKAN PROVINCE This study aimed to study factors affecting the demand forUsing accounting information that was beneficial with decision for marketing activities of Small and Medium Enterprise (SME) in SamutPrakanProvice. The samples in this study were marketing chiefs and owners of Small and Medium Enterprises (SMEs) in SamutPrakan Province. Selected a sample population consisting of 130 persons, was used as data collection in this study. The statistics of this study were frequency, percentage, mean, standard deviation, simple correlation, and multiple regression analysis. The result of this study found that 1) marketing chief were 20-25 years old, had graduated with Bachelor Degrees, at least 3 years’ experience in marketing field. Mostly, the organization had operated for 6– 10 years. The characteristics of organization were mostly service. The quality of accounting information that the owner needs was reliability 2) The demand for using accounting information in overall and each field was high level 3) The demand for using accounting information in overall and each field, werepositive relationship. 4) The variable of the factors affecting the demand for using accounting information were significantly found two compositions: Break-even Point Analysis( X18) and price of competitor (X21) which was written as equation as follows: The equation of raw scores Y^ = 1.141+ 0.31(X18) + 0.23(X21) The equation of standard scores Z ^ = 0..065(Z18) + 0.053(Z2)